An Assessment of Challenges to Local Governments and their Autonomy in Nigeria - Zango, Abdul-Aziz Sani; Mohammed, Isah Shehu (Kashere Journal of Politics and International Relations, 2025)
Grappling with multi-dimensioned challenges, agitation and struggle for autonomy by the local government have been a recurring phenomenon in the political history of Nigeria for several decades. Despite the age long struggle however, the desired result is yet to be achieved. This paper assesses the nature of local governments, their challenges and issues of granting them autonomy in the Nigeria. It also assesses the implications of those challenges on local governments’ administration. In this qualitative method of study, secondary sources of data are used. The paper found that that overcoming their challenges and the hope for autonomy for local governments is being impeded by several factors, including constitutional gaps, continuous political manipulation through the conduct of local elections, over-bearing interference and arbitrary control of the local governments’ funds, especially by the states’ governments and undue interferences in their local political, administrative, traditional and minor matters. These, have resulted in negative tendencies with direct negative implications on the local governments, the struggle to gain autonomy and effective and efficient operations. These hamper their drive to foster development through quality service delivery and relevant project execution within their areas of jurisdiction. The paper recommends strict constitutional laws relating to the local government, especially regarding their autonomy, avoidance of undue interference from the other levels of government, especially the states. Local governments should also be given the conducive atmosphere to perform independently with minimum control where necessary in terms sourcing and expending local revenues.